Peran Nilai Ketuhanan dalam Pancasila sebagai Fondasi Bangsa dalam Menghadapi Sekularisme Global - Paulin Alfantina Nelci; Yohanes Alexandro Waga; Bernadeta Febriana; Mario Faustinus Ceme To; Basilius Ileatan Maran; Maria Ranciana Bae; Teresia Bunga Karlince (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
As the first principle of Pancasila, Belief in the One and Only God holds a fundamental position in shaping the moral and spiritual direction of the Indonesian nation. Divinity serves not only as an ideological foundation but also as an ethical guideline guiding individual behavior and national life. In the current global context, where secularism is rapidly advancing and encouraging a separation between religion and the public sphere, the relevance of divinity is even stronger. Uncontrolled secularism has the potential to weaken the moral foundations of society, erode social solidarity, and trigger a value crisis that threatens national integrity. Divinity serves as a counterbalance to global trends often dominated by materialistic and individualistic views. In this situation, strengthening divinity principles is a strategic necessity, both in the formulation of public policy, the national education system, and in the practice of social life. Public policies based on divinity can ensure that development does not merely pursue economic growth, but also pays attention to social justice, shared prosperity, and the preservation of human values. In education, internalizing religious values encourages the development of students' character with integrity, respect for diversity, and high moral awareness. Meanwhile, in the social realm, the application of these values strengthens tolerance, maintains harmony between religious communities, and affirms unity in diversity. This article emphasizes that religious values are not merely normative ideological symbols, but rather pillars of national integration capable of addressing the challenges of the times. By reviving the spirit of Belief in the One and Only God in every aspect of life, Indonesia can confront the influence of global secularism without losing its spiritual identity, while simultaneously building a just, civilized, and sustainable society. In addition, the application of religious values in Pancasila also has strategic relevance in Indonesia's cultural diplomacy and foreign policy.